Effect of histidine on myocardial mitochondria and platelet aggregation during thrombotic cerebral ischemia in rats. - Li Shu-Qing; Zhao Gang; Li Jun; Qian Wei (Acta Pharmacologica Sinica; Vol 19, No 5 (September 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of histidine on cerebral thrombosis and possible mechanism. METHODS: Cerebral-cardiac stroke was produced by photochemically induced thrombotic cerebral ischemia in rats. RESULTS: Platelet aggregation in whole blood increased markedly, peak heights at 4 and 24 h were (5.1 +/- 0.5) omega and (4.3 +/- 0.5) omega, respectively. Heart mitochondria volume (V), volume density (Vv), surface density (Nm), and surface density of outer membrane (Sv1) increased (8.2 +/- 5.5, 0.59 +/- 0.16, 0.11 +/- 0.03, and 0.22 +/- 0.05, respectively, P < 0.01), but numerical density (Nv), specific surface of inner membrane (delta 2) and of the cristae (delta 3) decreased (0.07 +/- 0.02, 2.8 +/- 0.8, and 2.4 +/- 0.7, respectively, P < 0.01) after cerebral thrombosis. The myocardial histopathologic characteristics were different from those of ischemic necrosis and myocardial damage caused by ischemic reperfusion. In rat treated with histidine after photochemical reaction, platelet aggregation decreased markedly [(2.93 +/- 1.08) omega, P < 0.01], reversible change often went with parameters related to the inner mitochondrial membrane but not the outer mitochondrial membrane. CONCLUSION: Histidine depressed platelet aggregation and reduced myocardial mitochondrial damage resulted from cerebral ischemia.